2022
DOI: 10.31436/iiumej.v23i1.2119
|View full text |Cite
|
Sign up to set email alerts
|

Critical Success Factors for Building Information Modelling (Bim) Implementation for Power Plant Projects in Malaysia

Abstract: Building Information Modelling (BIM) has become increasingly important for the construction industry in Malaysia. BIM implementation process requires proper strategic planning and considerations from many aspects.Malaysian government has realised the importance of BIM as an emerging technology to transform the construction industry in Malaysia,and thus has classified BIM as one of the twelve main technology in  CIDB “Construction 4.0 Strategic Plan 2021-2025”. BIM implementation offer significant benefits to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…An area of deficiency that has been identified pertains to the necessity of scrutinizing the principal motivators and facilitators of Industry 4.0 implementation within the construction sector of China. Prior research has identified key factors crucial to driving successful digitalization efforts, including organizational culture, leadership support, and technological readiness [24]. Nevertheless, as mentioned earlier, these factors could exhibit distinct manifestations within the Chinese milieu, owing to the distinctive attributes and predicaments of the domestic construction sector [15,20].…”
Section: Related Workmentioning
confidence: 99%
“…An area of deficiency that has been identified pertains to the necessity of scrutinizing the principal motivators and facilitators of Industry 4.0 implementation within the construction sector of China. Prior research has identified key factors crucial to driving successful digitalization efforts, including organizational culture, leadership support, and technological readiness [24]. Nevertheless, as mentioned earlier, these factors could exhibit distinct manifestations within the Chinese milieu, owing to the distinctive attributes and predicaments of the domestic construction sector [15,20].…”
Section: Related Workmentioning
confidence: 99%
“…The top five most cited technologies and processes are BIM, cyber-physical systems, Internet of Things (IoT), automation, and robotics/industrial robots. Additionally, the five technologies and processes with the most publications and specific studies are BIM [43,44,[95][96][97][98][99][100][101][102][103][104][105][106][107][108], digital twins [21,92,[109][110][111][112][113][114], automation [19,20,76,[115][116][117][118], robotics [118][119][120][121][122][123][124], cybersecurity [41,42,[125][126][127][128], and Internet of Things (IoT) [75,[129][130]…”
Section: Synthesismentioning
confidence: 99%
“…The digitalization of design, construction, and management processes is already a consolidated reality through the use of Building Information Management (BIM) [95][96][97][98][99][100][101][102][103][104][105][106][107][108]. The integration of BIM with other technologies such as virtual reality (VR) and augmented reality (AR) means an advance in the visual representation and simulation of construction processes, allowing everything from improvements in business strategies (sales and contacts with potential customers) to the prediction of risk situations for workers [26][27][28][29][30][31][32].…”
Section: Synthesismentioning
confidence: 99%
“…Adopting green energy technologies can also encourage innovation in the energy production industry and create new job opportunities [5]. Due to the failure of renewable energy projects in Pakistan, it has been crucial for the country to overcome ecological complications and energy crises [1,6], and similarly, to improve energy productivity, which reduces carbon dioxide by adopting advanced technology and economic developments [7]. Many studies addressed that Pakistan is facing environmental issues [8].…”
Section: Introductionmentioning
confidence: 99%